2009
DOI: 10.1161/hypertensionaha.109.133983
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Negatively Modulate Reactive Oxygen Species Generation in Vascular Smooth Muscle Cells

Abstract: Abstract-In intact vessels, endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) act as an integrated system, possibly through reactive oxygen species (ROS). Using a coculture system we tested whether ECs modulate VSMC redox status by regulating activity of NAD(P)H oxidase and antioxidants. VSMC production of O 2 •Ϫ , H 2 O 2 , and NO was assessed using fluoroprobes and amplex-red. NAD(P)H oxidase subunit expression and oxidase activity were determined by Western blotting and chemiluminescence, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…ROS production is increased in VSMCs from resistance arteries of hypertensive patients, and this is associated with up-regulation of vascular Nox (75,112,142,207,213,233). The importance of Nox in human cardiovascular disease is supported by studies showing that polymorphisms in Nox subunits are associated with increased atherosclerosis and hypertension.…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%
“…ROS production is increased in VSMCs from resistance arteries of hypertensive patients, and this is associated with up-regulation of vascular Nox (75,112,142,207,213,233). The importance of Nox in human cardiovascular disease is supported by studies showing that polymorphisms in Nox subunits are associated with increased atherosclerosis and hypertension.…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%
“…80 It has been reported that Oxidative stress in hypertension R Rodrigo et al impaired thioredoxin expression in spontaneously hypertensive rats 81 and in endothelial cells negatively regulates ROS production in VSMC through thioredoxin upregulation. 82 Thus, thioredoxin could be an important therapeutic target for the prevention and treatment of oxidative stress and hypertension. [83][84][85] Recent studies have shown that the antioxidant effects of mildly elevated serum bilirubin levels may protect against diseases that are associated with oxidative stress 86 through mechanisms that decrease oxidative stress and increase NO levels.…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%
“…A complex mixture of endothelial autocoids involving NO, cyclooxygenase 2 products, hydroxyeicosatetraenoic acids, and NADPH oxidase-derived ROS appears to contribute to this effect. 49 Collectively, these observations suggest that a substantial part of the vascular but also cardiac effects of angiotensin II is a consequence of indirect actions involving the MRdependent induction and activation of NADPH oxidases. Similar observations, although largely based on pharmacological data, have been made for serotonin and the adrenoceptors: inhibition of the 5-HT(2B) receptor for serotonin reduced the ROS production and cardiac hypertrophy in response to angiotensin II.…”
Section: Brandes Vascular Functions Of Nadph Oxidasesmentioning
confidence: 98%